Hosting capacity and optimal sizing: a Colombian case of study - Diego Andrés González-Sotto; César Arango-Lemoine; Dahiana López-García; Adriana Arango-Manrique (Revista UIS Ingenierías)
The global energy transition has driven the adoption of renewable generation resources in distribution networks worldwide. This shift has presented new operational challenges for these networks. One such challenge involves determining the ideal sizing of these resources and the hosting capacity of the distribution networks to maximize their potential to enhance technical parameters within the system. This article proposes strategies to optimize the generation capacity and the selection of nodes in Colombian distribution networks, prioritizing nodes of lower voltage to improve reliability and continuity of supply. Specific methodologies are developed due to the passive and radial nature of these networks.